Acceptance of Industrial Collaborative Robots by People With Disabilities in Sheltered Workshops - Drolshagen, Sandra; Pfingsthorn, Max; Gliesche, Pascal; Hein, Andreas (Frontiers in Robotics and AI, 2021)
The inclusion of people with disability into the working world is an important, yet challenging field of research. While different inclusion efforts exist, people with disability are still underrepresented in the open labor market. This paper investigates the approach of using a collaborative robot arm in order to support people with disabilities and to foster their reintegration into the open labor market. However, little literature about the acceptance of an industrial robot by people with disability exists so far. In case a robot leads to stress, fear, or any other form of discomfort, this approach is infeasible. For this reason, this paper performed a first user study in a Sheltered Workshop for people with disability to investigate the acceptance of a robot arm by workers with disability. As a first step in this underdeveloped field, two main aspects were covered in this work. Firstly, the reaction and familiarization of the people with disability with a study situation involving a robot arm was closely examined in order to separate any effects that are not caused by the moving robot. Secondly, the reaction towards the robot arm during a collaboration was investigated. In doing so, five different distances between the robot arm and human were considered to make the collaboration as pleasant as possible. The results reveal that it takes the participants about 20 minutes to get used to the situation, while the robot was immediately accepted very well and did not cause fear or discomfort at any time. Surprisingly, close distances got accepted as good, and partly even better than larger distances. For these reasons, the presented approach showed to be promising for future investigations.